European radiographers’ challenges from mammography education and clinical practice: an integrative review - Metsälä, Eija (2017)
Objectives: This study aims to identify European radiographers' challenges in clinical performance in mammography and the main areas of mammography that require more and better training. Methods: An extensive search was performed to identify relevant studies focused on clinical practice, education and training in mammography published between January 2010 and December 2015 in the English language. The data were analyzed by using deductive thematic analysis. Results: A total of 27 full-text articles were read, evaluating their quality. Sixteen articles out of 27 were finally selected for this integrative review. The main challenges of radiographers’ mammography education/training can be divided into three groups: training needs, challenges related to radiographers, and challenges related to the organization of education. The most common challenges of clinical performance in mammography among European radiographers involved technical performance, the quality of practices, and patient-centeredness. Conclusions: The introduction of harmonized mammography guidelines across Europe may serve as an evidence-based tool to be implemented in practice and education. However, the variability in human and material resources, as well as the different cultural contexts, should be considered during this process.